CANONICAL CORRELATION ANALYSIS BETWEEN SPECIFIC-MOTOR AND PSYCHOLOGICAL ABILITIES WITH WRESTLERS - Shala Egzon; Nikći Valo; Zarko Kostovski (Sport Scientific And Practical Aspects, 2025)
The quality of wrestling sports results largely depends on the quality of the technique's performance (or techniques) and the psychological characteristics of athletes. For this reason, improving the psychological dimensions and increasing the efficiency of the technique is the basic task in the training process of the wrestlers. The survey was conducted on the sample of the top wrestlers from the Republic of Macedonia, Kosovo and Albania. The wrestlers who conduct a sample of 103 participants are at the age of 18.6 ± 0.6, and with average wrestling experience of 4.88 years of wrestling. In order to determine the relationship between different groups of variables, a canonical correlation analysis was made. From the analysis it was determined that statistically significant impacts in the performance of specific-motor tests have tests of visual specialization, perceptual reasoning and perceptual speed test and visualization.